(untitled) (Bangladesh Journal of Medical Science, 2016)
Background: The purpose of this paper is to describe an anatomical variation of the hand extensor on the little finger of the right hand which receives four tendons, condition unknown, as it is the first case reported so far in the literature. The human extensor tendons of hand often display an array of variations. Awareness of the anatomy and variations of the extensor tendons on the dorsum of the hand is necessary not only for the anatomist but also for surgeons when considering tendons for hand surgery, tendon rerouting or transplants. Materials and Methods: Bilateral anatomical variation in the upper limb was found during routine dissection in a 75-year-old male cadaver in the Morphology Laboratory at the University of Pamplona. The variations were recorded and photographed. Result: In the left hand the extensor digitorum there was a single tendon to the index, double tendon to the middle, triple tendon to the ring finger, a single tendon to the little finger or digiti minimi. The extensor digiti minimi has double tendon. In the right hand the extensor digitorum there was a single tendon to the index, triple tendon to the middle finger, triple tendons to the ring finger, a double tendon to the little finger. The extensor digiti minimi has double tendon. The little finger receives four tendons, 2 of extensor digitorum and 2 of extensor digiti minimi. The dorsum of the left hand and right showed juncturae tendinum type 2, between the extensors tendons in the 3rd intermetacarpal space; type 3, between the extensors tendons in the 4th inter metacarpal space. Conclusion: The presence of multiple tendons may alter the kinematics around the site of attachment to the phalanx. Knowledge of anatomical variations and normal anatomy of the extensor tendons, may be helpful while performing graft and tendon transfer operations. Bangladesh Journal of Medical Science Vol.15(2) 2016 p.278-282